Vowel representations in the invented spellings of Spanish-English bilingual kindergartners - Raynolds, Laura B.; Uhry, Joanna K.; Brunner, Jessica (Reading and Writing, 2013)
The study compared the invented spelling of vowels in kindergarten native Spanish speaking children with that of English monolinguals. It examined whether, after receiving phonics instruction for short vowels, the spelling of native Spanish-speaking kindergartners would contain phonological errors that were influenced by their first language. Results showed no differences between the two groups on the number of correct short vowel spellings, even though the sounds for four of the five English short vowels do not exist in Spanish. By contrast, differences were observed in the representation of long vowels with a higher rate of error among ELLs. The students had not received explicit instruction in long vowels. ELLs appeared to be trying to represent the diphthongized nature of some English long vowels by spelling long vowels with more than one vowel. The results support the authors' hypothesis that kindergarten phonics instruction had an impact on the invented spellings of new second language vowel phonemes.
15 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/031-056-476-891-636 tex.unique-id: [object Object]
Keywords: Bilingual; English language instruction; Invented spelling; Spanish language; dept.cur; peer-reviewed

Everyone has a story: A collaborative inquiry project by five teacher candidates of color and one white professor - Bower-Phipps, Laura; Tate, Rachel Watanabe; Mehta, Sejal; Sature, Amanda L (Current Issues in Education, 2013)
Initiatives to increase the number of teachers of color in U.S. public schools must be accompanied by culturally relevant teacher preparation for candidates of color. This study is a cooperative inquiry (Heron, 1996) conceived, conducted, and analyzed by five preservice teachers of color and one of their professors, a white lesbian. The women met biweekly for a year to co-construct meaning from their experiences in a teacher education program. They analyzed data sources together, including meeting transcripts, autobiographical sketches, and reflective writing on themes from the data. Key findings include the complexity of teacher candidates' identities; the importance of support systems for teacher candidates of color, particularly within predominantly white contexts; the connection between teacher candidates' backgrounds and their visions as teachers; and the role others' perceptions, particularly teacher educators, have played in teacher candidates becoming teachers.
Citation Key Alias: lens.org/033-975-273-700-369 tex.type: [object Object]
Keywords: Cooperative inquiry; Diversity; Teacher identity; Teachers of color; dept.cur; peer-reviewed; ⛔ No DOI found